2022
DOI: 10.3390/healthcare10030525
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Burnout and Depression, Psychological Well-Being as Predictor of Healthcare Professionals’ Turnover during the COVID-19 Pandemic: Study in a Pandemic Hospital

Abstract: Turnover of healthcare professionals’ is a rapidly growing human resource issue that affects healthcare systems. During the COVID-19 pandemic, healthcare professionals have faced stressful situations that have negatively impacted their psychological health. In this study, we explored impacts of the emotional wellbeing of healthcare professionals on their intention to quit their jobs. A cross-sectional survey design was used for this study. The respondents were selected based on simple random sampling. In total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 39 publications
1
50
0
3
Order By: Relevance
“…The COVID-19 pandemic has stressed health systems and health workers in an unprecedented way, inevitably causing a worsening of working conditions, with possible serious repercussions on the mental health conditions of workers [ 25 , 26 ]. However, the situation before the pandemic was not an optimal situation [ 10 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has stressed health systems and health workers in an unprecedented way, inevitably causing a worsening of working conditions, with possible serious repercussions on the mental health conditions of workers [ 25 , 26 ]. However, the situation before the pandemic was not an optimal situation [ 10 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Physio-psychological health and work performance may be adversely affected by persistent exposure to anxiety [ 34 ]. In another similar study, it was found that emotional stress impacted healthcare workers’ intentions to leave their jobs [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Copenhagen Burnout Inventory scale is a 7-question scale. It is often interpreted in a 3-group classification (<14: low, 14–20: medium and >20: high burnout) [ 24 ]. The PHQ-9 is a 9-depression question scale.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations